Technological innovation in the protection of beta carotene on MOCAF production which is rich in beta carotene - HARTATI HARTATI; AHMAD FATHONI; SITI KURNIAWATI; N. SRI HARTATI; ENNY SUDARMONOWATI (Smujo International, 2017)
Hartati, Fathoni A, Kurniawati S, Hartati NS, Sudarmonowati E. 2017. Technological innovation in the protection of beta carotene on MOCAF production which is rich in beta carotene. Nusantara Bioscience 9: 6-11. The conversion process of high beta carotene cassava into high beta carotene MOCAF might cause a high loss of beta carotene contents during the process of flour making. This research aims to develop the most appropriate technology to protect the loss of beta carotene contents during MOCAF process. Preservation methods used consisting of four starter treatment combinations of Bimo-CF and sodium metabisulfite (Na2S2O5) on Adira 1 variety, namely (i) 0.5 g starter/L volume of soaking solution and 0.3% of Na2S2O5, (ii) 0.5 g starter and 0.15% of Na2S2O5, (iii) 1 g starter and 0.3% of Na2S2O5, and (iv) 1 g starter and 0.15% of Na2S2O5. The results showed that Na2S2O5 can reduce the loss of beta carotene contents during the process of flour making. Of the initial concentration of beta carotene in tubers (3.5 mg/kg), the loss of beta carotene on MOCAF control without preservation process with Na2S2O5 reached 68.8% (1.09 mg/kg). With Na2S2O5 application, the loss of beta carotene could be reduced to 24.3% (2.65 mg/kg). The fermentation process with Bimo-CF starter increased the protein content of MOCAF two times from the control. The best and safest protection of beta carotene for food was achieved from preservation method using the combination of 1 g/L volume of soaking solution starter and 0.15% of Na2S2O5 which produced residue of Na2S2O5 to 53.07 mg/kg, which means lower than the maximum residue allowed in a flour product (70 mg/kg). The MOCAF yield obtained from each combination is quite high in range of 32-38%. The highest MOCAF yield is obtained from the protection method using combination of 1 g/L volume of starter soaking solution with Na2S2O5 0% and 0.15%.